What Determines E-Loyalty and E-Trust of Indonesian Muslim Lecturers Using Video Conference? - Munandar Munandar; Naufal Bachri; Chalirafi Chalirafi; Fuadi Fuadi (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
This study examines the effect of perceived privacy and perceived security on e-trust and e-loyalty of Muslim lecturers using video conference media. Additionally, the role of e-trust as a mediator in this relationship and the role of consumer innovativeness as a moderator of the relationship between e-trust and e-loyalty are investigated. The samples consisted of 250 respondents selected using a purposive sampling technique. The data was collected by a questionnaire survey and analyzed in AMOS using Structural Equation Modelling. The results indicate that perceived privacy and security considerably and favorably influenced e-trust. Similarly, e-trust and perceived privacy have a strong positive effect on e-loyalty, although perceived security has no effect. Moreover, e-trust could moderate the impact of perceived privacy on e-loyalty, but not the impact of perceived security on e-loyalty. Meanwhile, consumer innovation could not regulate the link between e-trust and e-loyalty. The findings have implications for establishing the concept of e-trust and customer innovativeness in the e-loyalty model.==========================================================================================================ABSTRAK – Apa Determinan E-Loyalitas dan E-Kepercayaan Dosen Muslim Indonesia dalam Menggunakan Video Conference? Penelitian ini menguji pengaruh persepsi privasi dan keamanan yang dirasakan terhadap e-kepercayaan dan e-loyalitas dosen muslim dalam menggunakan media video konferensi dan juga menguji peran e-kepercayaan sebagai mediasi dalam hubungan ini dan peran keinovatifan konsumen sebagai moderasi hubungan antara e-kepercayaan dan e-loyalitas. Sampel yang diambil sebanyak 250 responden dengan pendekatan purposive sampling dan metode analisis data yang digunakan adalah Structural Equation Modelling menggunakan AMOS. Hasil penelitian menunjukkan bahwa persepsi privasi dan persepsi keamanan berpengaruh positif dan signifikan terhadap e-kepercayaan. Persepsi privasi memiliki pengaruh positif dan signifikan terhadap e-loyalitas, persepsi keamanan tidak berpengaruh terhadap e-loyalitas, dan e-kepercayaan berpengaruh positif dan signifikan terhadap e-loyalitas. E-kepercayaan dapat memediasi efek privasi yang dirasakan pada e-loyalitas tetapi tidak memediasi pengaruh keamanan yang dirasakan pada e-loyalitas. Demikian juga, inovasi konsumen tidak dapat memoderasi hubungan e-kepercayaan terhadap e-loyalitas. Penelitian ini berimplikasi pada pengembangan konsep e-kepercayaan dan keinovatifan konsumen dalam model e-loyalitas.